2020
DOI: 10.5267/j.msl.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Social capital measurement based on “The value explorer” method

Abstract: The article substantiates the essence of the concept of "social capital" as a resource in terms of formed, permanent, established types of highly effective socio-economic interactions. In addition, the main directions of its manifestation and its structural elements are defined. It is stated that for quantitative measurement of social capital at the enterprise level, it is necessary to establish its precise framework, to determine its structure and key features. As an object of accounting, social capital shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…Andrusiv et al (2020) argue that innovation contributes to structural changes and economic development of regions. Ievdokymov et. al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Andrusiv et al (2020) argue that innovation contributes to structural changes and economic development of regions. Ievdokymov et. al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most popular stablecoins are represented in the form of Tether (USDT) or "digital dollar"; Didig (DGX) or "digital gold"; El Petro or "digital oil". Nowadays, development in digital technology affects the changes not only in the technologies dealing with goods and service payment operations but also people's attitude to that process (Ievdokymov et al, 2020). One generation replaces another, modern society experiences constant transformations.…”
Section: Resultsmentioning
confidence: 99%
“…Galan-Muros and Davey (2019) talked about bilateral relationship between universities and business and argue in their work that this collaboration is currently fragmentary. Leonchuk and Gray (2019) and Ievdokymov et al (2020) explored the understanding of outcomes and results of science, technology and innovation through human capital, using a rare quasi-experimental method in two ways: traditional and non-center learning. Belyaeva and Belyaev (2019) conducted a study of the behavior of stakeholders at universities in Russia and China and identified a number of factors that influence the functioning of interaction between Russian and Chinese student structure: geopolitical situation, cost and quality of education, adaptation of courses for international students, comfort of the university's learning environment, the complexity of learning the language of the host country, the prestige of education.…”
Section: Literature Reviewmentioning
confidence: 99%